The The Implementatıon Of Green Actıvıtıes Among Mıcro And Small Enterprıses: A Factor Analysıs Approach - Jerico Tadeo; Xavier Lawrence Mendoza; Jennifer A. Basanes; Jeraldine M. Jimenez; Leanne Vhines T. Serrano (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Micro and small enterprises became one of the significant economic contributors of several countries to develop entrepreneurship, employment opportunities, and reducing poverty. Through a factor analysis design, the researchers aimed to understand the strategy implementation of green activities among the selected micro and small enterprises. The researchers utilized a descriptive-causal research design in conducting the study. Moreover, the study used a convenience sampling design to acquire 40 respondents who implement green activities from the municipalities of Imus, General Trias, and Tanza, Cavite. The researchers asked respondents through a researcher-made questionnaire that was distributed through online forms. The findings revealed that most green MSEs are sole proprietors, have an average asset size of below 3 million, have less than ten employees, and are in 1-3 years of business operation. Most MSEs ensure that they offer products that do not contain hazardous materials. The study used the Chi-square test, Tucker-Lewis Index (TLI), RMSEA, R-squared, and factor loadings to determine, synthesize and maximize significant associations of the variables to strategy implementation of green activities among MSEs. Thus, the result of the study provides marketing insights concerning to proposed and maximized prototype business model. The study recommends that enterprises apply green practices to achieve organizational goals while considering environmental sustainability.